EVALUATION OF THE NATURAL CONDITIONS AND RESOURCES OF UZBEKISTAN FROM THE ECONOMIC GEOGRAPHICAL POINT OF VIEW - Salohiddinov Bunyod, (TADQIQOTLAR.UZ, 2023)
Abstract: This article talks about the geographical location of the Republic of Uzbekistan, its influence in the world community, foreign economic relations, export and import opportunities. The current state of foreign economic relations, proposals, aspects that should be paid attention to, and legal bases are highlighted.